2010
DOI: 10.3109/08941930903469425
|View full text |Cite
|
Sign up to set email alerts
|

Integrins and Monocyte Migration to the Ischemic Myocardium

Abstract: Significant ED1+ mononuclear cell migration within 24 hr of MI correlated with peak MCP-1 mRNA. Monoclonal antibody blockade suggested that early mononuclear cell migration is dependent only in part on alpha4 and beta2 integrins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The early stage of myocardial infarction involves massive infiltration of inflammatory cells mainly into the peri-infarct region [18]. Macrophages play a role in the removal of the necrotic tissue and in the initiation of a healing process.…”
Section: Discussionmentioning
confidence: 99%
“…The early stage of myocardial infarction involves massive infiltration of inflammatory cells mainly into the peri-infarct region [18]. Macrophages play a role in the removal of the necrotic tissue and in the initiation of a healing process.…”
Section: Discussionmentioning
confidence: 99%
“…This process has been shown to be critically mediated by monocytes, which mature to active macrophages at the inflammatory site. Thus, monocytes have recently drawn considerable attention as a target to improve post-AMI repair [1, 2]. It has recently been demonstrated that CD14 + - expressing macrophages predominantly accumulate at the infarct zone twelve hours- five days following the ischemic event [3].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have demonstrated that monocytes play a key role in atherosclerosis [6,7], myocardial infarction (MI) [8], and healing after MI [9]. Monocytes are attracted to the coronary artery wall, where they differentiate to macrophages, become loaded with lipids, and remain trapped there.…”
Section: Introductionmentioning
confidence: 99%